Implementasi Web Portal Pageraji.info Untuk Mengangkat Potensi Desa Pageraji Kecamatan Cilongok Kabupaten Banyumas - Trias Bratakusuma; Zanuar Rifai; Ratna Arvianti Saputri (Politeknik Negeri Cilacap, 2020)
The village is a community that has the authority to regulate and regulate the community on the basis of proposals and customs as precisely as discussed in the national government system and is in the Regency. Each village has different potential. Village Potential is all natural resources and human resources that are provided at the same time stored in the Village. Pageraji Village is located in the West of the Capital City of Banyumas Regency with a distance of approximately 9 km and consists of lowland and plateau areas bordering the North of Langgongsari Village, East of Langgongsari Village and Pejogol Village, in the South of Jatisaba Village, Kasegeran Village and Desa Sudimara, west of Cilongok Village and Pernasidi Village. The current economic condition of Pageraji Village is supported by the agriculture, livestock, fisheries, trade and home industries and services sectors. Pageraji Village has a lot of village potential in terms of culture, tourism, culinary, local wisdom and others. However, the potential of Pageraji Village has not yet been raised because it has not found the most appropriate media to support the existing potential. Currently Internet users in Indonesia are more than 50 percent or around 143 million people throughout 2017 according to the latest report by the Indonesian Internet Service Providers Association (APJII). The majority of internet users as much as 72.41 percent are still from urban communities. Pageraji.info Web Portal to support the potentials in Pageraji Village both in terms of culture, tourism, culinary, local wisdom and others. Enabling the potential of Pageraji Village can be lifted well because there is the most appropriate media to support the existing potential.